2023
DOI: 10.3171/2022.11.focus22614
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial subsecond dopamine measurements during a “sure bet or gamble” decision-making task in patients with alcohol use disorder suggest diminished dopaminergic signals about relief

Abstract: OBJECTIVE To the authors’ knowledge, no data have been reported on dopamine fluctuations on subsecond timescales in humans with alcohol use disorder (AUD). In this study, dopamine release was monitored in 2 patients with and 2 without a history of AUD during a “sure bet or gamble” (SBORG) decision-making task to begin to characterize how subsecond dopamine responses to counterfactual information, related to psychological notions of regret and relief, in AUD may be altered. METHODS Measurements of extracellul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Our group recently demonstrated that sub-second dopamine fluctuations in response to calculated relief values effectively separated patients with and without Alcohol Use Disorder (AUD). 19 Here we expand this approach to propose sub-second dopamine fluctuations from the dorsal striatum as potential future investigative anatomic structures for preclinical work on the origins of ICD. Our sample size was modest (n = 3 patients with ICD, n = patients without ICD), but our results align with previous human neuroimaging studies demonstrating dorsal striatal activation during risky decision-making in patients with ICD.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our group recently demonstrated that sub-second dopamine fluctuations in response to calculated relief values effectively separated patients with and without Alcohol Use Disorder (AUD). 19 Here we expand this approach to propose sub-second dopamine fluctuations from the dorsal striatum as potential future investigative anatomic structures for preclinical work on the origins of ICD. Our sample size was modest (n = 3 patients with ICD, n = patients without ICD), but our results align with previous human neuroimaging studies demonstrating dorsal striatal activation during risky decision-making in patients with ICD.…”
Section: Discussionmentioning
confidence: 99%
“…1012 The insights gained by presenting sub-second dopamine fluctuations measured in the human operating room offer potential mechanisms underlying this debilitating behavioral addiction disorder for future neuroimaging and other pre-clinical work. 19…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations